Nematocidal Activity of a Variety of Plants Used in Mexico Against Strongyloides venezuelensis - Joel H. Elizondo-Luévano; Abelardo Chávez-Montes; Antonio Muro; Belén Vicente-Santiago; Miroslava Kačániová; David G. García-Hernández; Aldo F. Bazaldúa-Rodríguez; Horacio Larqué-García; Uziel Castillo-Velázquez; Julio López-Abán (Parasitologia, 2025)
Strongyloidiasis represents a public health problem in tropical and subtropical regions. The medicinal plants demonstrate the potential of plants as a source of molecules with helminthic activity. In this research, we assessed the potential of five extracts medicinally used in Mexico against Strongyloides venezuelensis third-stage infective larvae (L3). Plant methanol (MeOH) extracts of Argemone mexicana (chicalote), Jatropha dioica (Sangre de Drago), Lippia graveolens (oregano), Thymus vulgaris (tomillo), and Kalanchoe daigremontiana (aranto) were prepared by the maceration technique. The toxicity of the extracts was evaluated in human red blood cells by the hemolysis test and in monkey kidney epithelial cells (Vero cells) using the reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. In addition, we showed their antioxidant potential by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The methanolic extracts of A. mexicana, J. dioica, L. graveolens, and T. vulgaris exhibited significant activity against L3 cultures at 72 and 96 h post-incubation. None of the extracts showed hemolytic effects on red cells or Vero cells. L. graveolens demonstrated the strongest antioxidant activity, with an EC50 of 19.80 µg/mL. Plant MeOH extracts used in this study showed a promising anthelmintic effect in vitro, making it a suitable candidate for future research in nematocidal therapies.